2014
DOI: 10.4081/rt.2014.5404
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Drop Metastasis in Myxopapillary Ependymoma: A Case Report and a Review of Treatment Options

Abstract: Myxopapillary ependymoma (MPE) is a World Health Organization grade I ependymoma that is quite rare and generally thought to be benign. Possible drop metastasis from MPE has been reported three times in the literature; in each case there were cotemporaneous additional MPE lesions. We report the case of a man who had a piecemeal gross total resection of a MPE at L1-L3 followed by adjuvant external beam radiotherapy (EBRT) who presented sixteen months later with a lesion in the thecal sac consistent with drop me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…An additional case report describes a 22-year-old man who presented with MPE lesions in the third ventricle and sacral spinal canal; he was hypothesized to have a drop metastasis by the authors, though both lesions were again found simultaneously (13). There has been only one previously reported case where an adult patient presented with secondary MPE drop metastases following an initial subtotal resection and post-operative radiotherapy of the tumor bed of a primary MPE similar to our case (16). To our knowledge this is the only reported case in literature of a MPE with interval drop metastasis presenting as cauda equina syndrome.…”
Section: A B Csupporting
confidence: 64%
“…An additional case report describes a 22-year-old man who presented with MPE lesions in the third ventricle and sacral spinal canal; he was hypothesized to have a drop metastasis by the authors, though both lesions were again found simultaneously (13). There has been only one previously reported case where an adult patient presented with secondary MPE drop metastases following an initial subtotal resection and post-operative radiotherapy of the tumor bed of a primary MPE similar to our case (16). To our knowledge this is the only reported case in literature of a MPE with interval drop metastasis presenting as cauda equina syndrome.…”
Section: A B Csupporting
confidence: 64%
“… [7] and Bates et al. [8] . the latter case was subjected to second surgery for metastasis resection.…”
Section: Discussionmentioning
confidence: 97%
“…Ependymal tumors originate from ependymal cell rests and are uncommon central nervous system neoplasms with an incidence of 0.2/100,000 person-years and a slight predominance in men and Caucasians. [5,16] It has been described a slight upward trend over the past 35 years. [5] Ependymal tumors usually appear in the fourth decade of life, and in adults, 75% occur in the spinal canal, making up 25% of intramedullary spinal cord tumors and 2% of primary central nervous system neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…[5,16] It has been described a slight upward trend over the past 35 years. [5] Ependymal tumors usually appear in the fourth decade of life, and in adults, 75% occur in the spinal canal, making up 25% of intramedullary spinal cord tumors and 2% of primary central nervous system neoplasms. [3,6] No specific risk factors have been identified; however, associations with neurofibromatosis type 2, SV-40 polyomavirus exposure, and the lack of vitamin intake in the prenatal period by the mother have been suggested.…”
Section: Discussionmentioning
confidence: 99%